BUSINESS STRATEGIES IN IMPROVING COMPETITIVENESS: ITS IMPACT ON BUSINESS PERFORMANCE - Ilham Karin Rizkiawan; Nurul Aisah; Fahman Hadi Utomo; Aulia Uswatun Khasanah (FE Program Studi Manajemen, 2026)
This study aims to identify the impact of coffee shop business strategies in increasing competitiveness on business performance.This study evaluates the factors of proactiveness, risk-taking, and innovation among coffee shop business owners in Soloraya. The problem in this study is the increasing prevalence of coffee-drinking culture that makes coffee shops unable to survive in business competition due to oversupply, as well as the prevalence of consumer behavior that is easily bored so that loyalty to a product tends to decrease.The object of the study was coffee shop owners in Soloraya, involving 90 respondents as a sample. This study used a quantitative method using SmartPLS for data processing. The findings show that business strategy factors, including proactiveness, risk-taking, and innovation, have a significant positive effect on business performance. Coffee shop owners need to apply the right concept and target determination to be able to increasingly innovate in following consumer tastes